Single stage reconstructions in head and neck surgery using deltopectoral and pectoralis major myocutaneous flaps - Nayak, Bibhuti B. (Medknow Publications & Media Pvt Ltd, 2012)
Even though free tissue transfers are a routine in many centres, pedicle flaps still have a huge roll to play in our country. There are many centres in the country where pedicle flaps are in use because of logistic problems. Deltopectoral and pectoralis muscle flaps are usually preferred for composite cheek defects. When both these flaps are used in combination it is a two-staged procedure. We describe a single-stage procedure to reconstruct a composite cheek defect with pectoralis major myocutaneous flap for lining and single-stage deltopectoral flap for cover. In the available literature search, single-stage DP and PMMC have not been described for management of composite cheek defect.